The encryption algorithms GOST28147–89–IDEA8–4 and GOST28147–89–RFWKIDEA8–4 - Tuychiev, Gulom Numovych (Ukrainian Information Security Research Journal, 2017)
In this paper there were created new encryption algorithms GOST28147–89–IDEA8–4 and GOST28147–89–RFWKIDEA8–4 based on networks IDEA8–4 and RFWKIDEA8–4, with the use the round function of the encryption algorithm GOST 28147–89. The block length of encryption algorithm is 256 bits, the number of rounds is 8, 12, 16 and length of the key switches from 256 to 1024 bits. Depending on information privacy and encryption speed can we choose the number of rounds and key length. In the encryption algorithms encryption and decryption use the same algorithm, only when decryption calculates the inverse of round keys depending on operations and they are applied in reverse order.